Chets asked if 4+sqrt(5)*sqrt(3) = 1/(4-sqrt(5)*sqrt(3)) can be extrapolated into a broad generalization. No, it can't be!

Here's why.

Consider an expression \(1/(a-\sqrt{bc})\) [modeled on 1/(4-sqrt(5)*sqrt(3)) ]

Multiplying Numerator and Denominator with \((a+ \sqrt{bc})\), we get

\((a+ \sqrt{bc})/(a^2-bc)\)

So, the reason why 1/(4-sqrt(5)*sqrt(3) got simplified into 4+sqrt(5)*sqrt(3) was because the Denominator of the above expression is equal to 1 in this particular case (a=4, b=5, c=3. So,\(a^2-bc = 4^2-5*3 = 1\))

_________________

Please press Kudos if you were helped by my post!